The Impact of Career Development on Employee’s Commitment At Oil Palm Plantation Company In Indonesia - Srimulatsih, Mahbubah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
This study aims to determine whether career development has an effect on employee commitment. This research is important for the sustainability of a company. This study adopted a quantitative analysis using simple regression analysis. The population of this study was 43 employees that are working at one of Oil Palm Plantation Company in Riau, Indonesia. Sampling frame was the list of employees working in all levels of management. Quota sampling was applied in carrying out to conduct the study. Collecting data in this study using questionnaires conducted by distributing questionnaires to the respondents. The data analysis tool (Statistical Package for Social Sciences (SPSS Version. 21.0) was used to analyze quantitative data and results. Finding indicated that there was the influence of career development on employee commitment. It also indicated that career development contributed to the increase in employee commitment. The better the career development program in one organization occur , the better the commitment of employee for that organization.